The house - Bordeaux, Henry, 1870-1963; Houghton, Louise Seymour, 1838-1920 (Salt Lake City, UT : Project Gutenberg, 2023)
"The House" by Henry Bordeaux is a novel written in the early 20th century. The book explores themes of nostalgia and the significance of home through the eyes of the narrator, who reflects on his childhood experiences and the familial connections to a particular house where his family has lived for generations. The narrative emphasizes the emotional weight of "the house" as a symbol of memory and belonging, contrasting the idealized past with the changes brought by time. The opening of the novel introduces the narrator's deep affection for his childhood home, referred to simply as "the house." The young narrator recounts how various people, regardless of their station, refer to it with reverence and affection, signifying its central place in their lives. He nostalgically describes the house's features, changes over time, and the memories associated with it, highlighting the importance of the spaces we inhabit. As he reminisces, he conveys the innocence of childhood wonder, the influence of family dynamics, and the lingering impact of those memories on his adult perspective. (This is an automatically generated summary.)
Release date is 2023-12-12
Laura Natal Rodrigues (Images generously made available by Hathi Trust Digital Library.)
Keywords: French fiction -- Translations into English